2016
DOI: 10.1111/cmi.12665
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of cell wall mannan in the conidium and the mycelium ofAspergillusfumigatus

Abstract: The galactomannan is a major cell wall molecule of Aspergillus fumigatus. This molecule is composed of a linear mannan with a repeating unit composed of four α1,6 and α1,2 linked mannose with side chains of galactofuran. To obtain a better understanding of the mannan biosynthesis in A. fumigatus, it was decided to undertake the successive deletion of the 11 genes which are putative orthologs of the mannosyltransferases responsible for establishing α1,6 and α1,2 mannose linkages in yeast. These deletions did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 49 publications
2
69
3
Order By: Relevance
“…Eleven putative mannosyltransferases have been detected in A. fumigatus as orthologous genes in yeast responsible for establishing α-1,6and α-1,2-mannose linkages. However, the complete deletion of these genes did not lead to a reduction in the mycelial cell wall mannan content but caused a decrease in the mannan content of the conidial cell wall (Henry et al, 2016). Other orthologous genes of yeast mannosyltransferases, with a function not associated with mannan polymerization, were investigated and two members of the KTR family (also named Kre2/Mnt1) were found to be responsible for the polymerization of the structural cell wall galactomannan in this mold.…”
Section: Composition and Biosynthesismentioning
confidence: 97%
“…Eleven putative mannosyltransferases have been detected in A. fumigatus as orthologous genes in yeast responsible for establishing α-1,6and α-1,2-mannose linkages. However, the complete deletion of these genes did not lead to a reduction in the mycelial cell wall mannan content but caused a decrease in the mannan content of the conidial cell wall (Henry et al, 2016). Other orthologous genes of yeast mannosyltransferases, with a function not associated with mannan polymerization, were investigated and two members of the KTR family (also named Kre2/Mnt1) were found to be responsible for the polymerization of the structural cell wall galactomannan in this mold.…”
Section: Composition and Biosynthesismentioning
confidence: 97%
“…Although the mannan structural organization of fungi can differ substantially, a comparative genomic study has indicated that orthologues of most yeast mannosyltransferase genes can be found in the genome of A. fumigatus and other filamentous molds, although other branched chain mannans do not seem to be represented in the genome of Pneumocystis and possibly other fungi (56). In A. fumigatus, deletion of 11 genes coding for putative mannosyltransferases had little effect on the growth or physiology of A. fumigatus (57).…”
Section: Biosynthesis Of Mannan and Other Decorating Polysaccharidesmentioning
confidence: 99%
“…The long mannan chains are synthesized in yeasts by the α mannosyltransferase complex I and II, localized in the endoplasmic reticulum and Golgi vesicles. In A. fumigatus , the synthesis of the mannan moiety of A. fumigatus galactomannan follows another pathway that is still unknown [ 28 ]. The deletion of the 11 genes which are putative orthologs of the yeast mannosyltransferases did not lead to a reduction of the mannan content of the cell wall of the mycelium of A. fumigatus .…”
Section: The Outer Layer Of the Cell Wall Is A Protective Barriermentioning
confidence: 99%